Kinematics Analysis of 1T3R Parallel Mechanism with Decoupling-reducing Structure based on Hybrid Drive - Guowang Chen; Li Du; Linxian Che; Junkun Hong; Mafei Bao (Jixie chuandong)
Based on the position feature set theory and decoupling principle of parallel mechanism, a new kind of structure decoupled parallel mechanism with hybrid driving and local motion decoupling is designed and its movement is one translation and three rotations (1T3R). The topological structure of the parallel mechanism is analyzed, the type of the position feature set of the moving platform is obtained and the degrees of freedom and coupling of the mechanism are solved. The explicit analytical expressions of the positive and inverse solutions of the position of the mechanism are obtained by using the spatial projection principle and the pose transformation matrix method. The numerical examples of the positive and inverse solutions of the position of the mechanism are obtained by using MATLAB software programming and the results are completely consistent, indicating that the position inverse solution model is correct and reliable. The angular displacement curves of the mechanism are obtained by using MATLAB software programming and Adams software motion simulation and their results are the same, which verifies the correctness of the theoretical analysis model of motion. Based on the 3D motion simulation model, the angular velocity and angular acceleration curves of the mechanism are obtained.